The Role of AI in Health Research: A Policy Review of Higher Education Foundations - Yuris Tri Naili; Efendi Lod Simanjuntak; Anatoly Kostruba (Peneliti Teknologi Teknik Indonesia, 2024)
The integration of Artificial Intelligence in health research has transformed data analysis, predictive modeling, and personalized treatment strategies. However, its rapid adoption presents regulatory, ethical, and institutional challenges, particularly in higher education foundations that oversee health research. This paper examines policies governing AI-driven health research, focusing on regulatory frameworks, ethical guidelines, and institutional policies that shape AI applications in academia. At the global and national levels, regulations such as the EU AI Act and World Health Organization guidelines set standards for AI safety, transparency, and data protection in health research. Despite these frameworks, challenges persist, including data privacy concerns, algorithmic bias, and inconsistent ethical oversight. Ethical frameworks like the Ethical Regulatory Framework for AI emphasize accountability, fairness, and continuous monitoring to ensure responsible AI deployment. Higher education institutions play a crucial role in developing AI governance frameworks that balance innovation with compliance. However, inconsistencies in institutional policies create gaps in regulatory enforcement and ethical standards. Addressing these issues requires harmonized policies, interdisciplinary collaboration, and proactive stakeholder engagement. This paper highlights the role of AI in optimizing research methodologies, funding allocation, and regulatory compliance while discussing emerging challenges and future directions for AI-driven health research governance.